NANOTECHNOLOGY IN BIOMEDICAL ENGINEERING: ENHANCING DRUG DELIVERY SYSTEMS - Jaiswal, Shweta; Jaiswal, Ayush (ShodhKosh: Journal of Visual and Performing Arts, 2023)
Nanotechnology has transformed drug delivery systems. It offers innovative approaches to increase therapeutic efficacy and also reduces its side effects. This paper explores the application of nanotechnology in biomedical engineering, and it specifically focuses on improving drug delivery systems in India. The paper examines different principles such as quantum confinement, diffusion, and surface area-to-volume ratios which underpin nanoparticle designs and their interaction with biological systems. The paper highlights recent advancements like targeted delivery mechanisms and the development of nanoparticles, which improve stability of drug and release kinetics. The study also addresses some key challenges of nanotechnology like higher research and development costs, regulatory hurdles, and safety concerns. Study also proposes solutions to overcome these barriers. By analysing current trends and prospects, this paper aims to provide a comprehensive overview about how nanotechnology can address critical healthcare needs in India, especially for diseases like cancer and drug-resistant infections. The findings suggest that nanotechnology has significant potential to transform drug-delivery systems and to improve patient outcomes in India with strategic investments in research, improved regulatory frameworks, and increased collaboration between public and private sectors.